Neuroethics. Critical considerations - Madonna, Federica (Medicina e Morale, 2022)
This essay is based on some critical reflections concerning the nascent research direction, with the aim of highlighting the contradictions of a "scientific humanism" of which neuroethics would like to be the spokesperson. The analysis tends to show the new direction is an integral part of a broader conceptual framework (Bioethics), but also the resultant - in some aspects - of an attempt to restore the epistemology and ontology of the Modern era.